Defense Mechanisms versus Openness to Experience: Implications for Counselling - Liburd, Rosemary (Canadian Journal of Counselling and Psychotherapy, 2015)
A comparison is made of theories that view defense mechanisms as adaptive processes that promote mental health and those that define absence of defense and openness as criteria of positive life adjustment. Adaptive functions of defense mechanisms are related to providing stability and continuity, protection against intolerable anxiety levels and maintenance of an adequate self-concept. The alternate viewpoint defines defensive processes as antithetical to growth and regards the optimally functioning person as defense-free and open to experience. The author examines the implications of these theoretical models for counselling in relation to the following issues: ( 1 ) the openness of the counsellor in the counselling relationship, (2) a view of openness as a form of defense, and (3) dealing with defenses as part of the therapeutic process.